HUBUNGAN KECEMASAN DENGAN KUALITAS TIDUR PADA PASIEN PRE OPERASI TRANSURETHRAL RESECTION OF THE PROSTATE (TURP) DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Siburian, Christine Handayani (Universitas Murni Teguh, 2021)
Benign Prostatic Hyperplasia (BPH) is an enlargement of the prostate gland that generally occurs in older men and if left untreated can lead to complications. BPH can be treated with a medical procedure, namely the Transurethral Resection of the Prostate (TURP) surgical procedure. Before the action, the patient will experience anxiety. Anxiety arises because of excessive fear that can affect the quality of sleep. The purpose of this study was to determine the relationship between anxiety and sleep quality in patients with preoperative Transurethral Resection of the Prostate (TURP). The research design used was cross sectional. The sample is 31 respondents of preoperative patients at Rumah Sakit Umum Imelda Pekerja Indonesia Medan with the sampling technique used is accidental sampling. The research data was collected using the Hamilton Scale for Anxiety (HRS-A) questionnaire and The Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed by Spearman Rho correlation test. The results showed that there was a relationship between anxiety and sleep quality in patients with preoperative Transurethral Resection of the Prostate (TURP) (p=0.000, r=0.907). The results of this study can recommend that the need for nursing actions that can reduce anxiety so that the patient's sleep quality can be better. Abstrak Benign Prostatic Hyperplasia (BPH) adalah pembesaran kelenjar prostat yang pada umumnya terjadi pada pria yang lebih tua dan apabila tidak diobati dapat menyebabkan komplikasi. BPH dapat ditangani dengan tindakan medis yaitu prosedur pembedahan Transurethral Resection of the Prostate (TURP). Sebelum dilakukan tindakan tersebut, pasien akan mengalami kecemasan. Kecemasan timbul karena rasa takut berlebih yang dapat mempengaruhi kualitas tidur. Tujuan penelitian ini adalah mengetahui hubungan kecemasan dengan kualitas tidur pada pasien pre operasi Transurethral Resection of the Prostate (TURP). Desain penelitian yang digunakan Cross Sectional. Sampel adalah 31 responden pasien pre operasi di Rumah Sakit Umum Imelda Pekerja Indonesia Medan dengan teknik pengambilan sampel adalah teknik accidental sampling. Pengumpulan data penelitian menggunakan kuesioner Hamilton Scale for Anxiety (HRS-A) dan kuesioner The Pittsburgh Sleep Quality Index (PSQI). Data dianalisis dengan uji korelasi Spearman Rho. Hasil didapatkan ada hubungan kecemasan dengan kualitas tidur pada pasien pre operasi Transurethral Resection of the Prostate (TURP) (p=0,000, r=0,907). Hasil penelitian ini dapat merekomendasikan bahwa perlunya tindakan keperawatan yang dapat mengurangi kecemasan agar kualitas tidur pasien dapat menjadi lebih baik.